2013
DOI: 10.4028/www.scientific.net/amr.807-809.2583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Proppant Transport Performance of GRF-CO<sub>2</sub> Fracturing Fluid

Abstract: In this article, the experimental study on proppant transport performance of GRF-CO2 system is performed by using the large-scale foam fracturing fluid test system of high temperature and high pressure, and critical settling velocity and proppant settling velocity are obtained.Research results show that the critical settling velocity increases with the temperature rising, in foaming cases,decreases with the foam quality and sand ratio rising.The correlations for GRF-CO2 fracturing final proppant settling veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Particularly in China, the unconventional petroleum and gas resource is spectacular, which is about 240 × 10 8 t and 100 × 10 12 m 3 , respectively. Using proppants in the mining process can effectively improve the production of unconventional petroleum and gas. , However, previously reported coated proppants lost liquid conductivity quickly under higher pressure, leading to the necessity to develop coating proppants with high liquid conduction to meet the condition of complex and complicated cracks in shale rocks. A previous study indicated that the difficulty of mining is directly related to fracture conductivity of the proppant structure and the size as well as the complexity of the fracture network in unconventional petroleum and gas shale reservoirs .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in China, the unconventional petroleum and gas resource is spectacular, which is about 240 × 10 8 t and 100 × 10 12 m 3 , respectively. Using proppants in the mining process can effectively improve the production of unconventional petroleum and gas. , However, previously reported coated proppants lost liquid conductivity quickly under higher pressure, leading to the necessity to develop coating proppants with high liquid conduction to meet the condition of complex and complicated cracks in shale rocks. A previous study indicated that the difficulty of mining is directly related to fracture conductivity of the proppant structure and the size as well as the complexity of the fracture network in unconventional petroleum and gas shale reservoirs .…”
Section: Introductionmentioning
confidence: 99%